KEPEMIMPINAN VISIONER DALAM MEMBANGUN KOMUNITAS BELAJAR KOLABORATIF (Sindoro: Cendikia Pendidikan, 2025)
Penelitian ini bertujuan untuk mengkaji peran kepemimpinan visioner dalam membangun komunitas belajar kolaboratif di lingkungan pendidikan. Menggunakan pendekatan kualitatif deskriptif dengan metode studi pustaka, penelitian ini menganalisis berbagai literatur relevan terkait kepemimpinan visioner dan pengembangan komunitas pembelajaran. Hasil kajian menunjukkan bahwa kepemimpinan visioner memiliki kontribusi signifikan dalam menciptakan budaya kolaboratif yang kuat, memotivasi keterlibatan aktif anggota komunitas, serta mendorong inovasi dan pengembangan profesional secara berkelanjutan. Pemimpin visioner tidak hanya menyusun visi jangka panjang yang jelas dan inspiratif, tetapi juga mampu menggerakkan seluruh elemen pendidikan untuk bekerja bersama mencapai tujuan bersama. Penelitian ini menyimpulkan bahwa kepemimpinan visioner merupakan kunci dalam membentuk komunitas belajar yang inklusif, adaptif terhadap perubahan, dan berorientasi pada peningkatan mutu pendidikan.This research explores the importance of visionary leadership in shaping collaborative learning communities in educational settings. Using a descriptive qualitative research method through a literature study, a variety of literature discussing the concept of visionary leadership and learning community development was analyzed. The findings show that visionary leaders play a central role in instilling a strong culture of collaboration, encouraging active involvement of all elements of the school, and strengthening continuous innovation and professional growth. Visionary leadership goes beyond crafting an inspiring long-term vision, but is also able to mobilize all components of education to jointly actualize a common goal. In this context, visionary leaders act as drivers of change, facilitators of learning and guardians of collective spirit. Learning communities guided by a clear and implementable vision tend to be more adaptive to the dynamics of the times and have the ability to adopt innovative and relevant learning approaches. Thus, it can be concluded that visionary leadership is the main foundation in creating learning communities that are inclusive, participatory and oriented towards improving the overall quality of education. Its contribution not only includes increased collaboration and professionalism, but also has a direct impact on the successful achievement of long-term educational goals.